Development finance at a crossroads: After Seville and beyond - George Mavrotas (University of Athens, Department of Economics, International Economics and Development Laboratory (IEDL), 2025)
Development finance is facing mounting pressures amid global economic shocks, the lingering effects of the COVID-19 pandemic, and rising geopolitical tensions. These challenges have disrupted progress toward the Sustainable Development Goals (SDGs) and exposed vulnerabilities in the current financing architecture. The 4th Financing for Development Conference, held in Seville in July 2025, marked a renewed effort to mobilize political commitment and reorient strategies to address these setbacks. Inspired by the precedent set by the 2002 Monterrey Conference, the Seville gathering underscored the need for more pragmatic, accountable, and results-driven approaches. While Monterrey succeeded in galvanizing international support for the Millennium Development Goals (MDGs), its limitations revealed that political momentum must be matched by sustained implementation and realistic planning. In today's more volatile global environment, these lessons are even more critical. As the 2030 deadline approaches, there is growing consensus that development finance must be recalibrated to reflect current realities-through adaptive, context-sensitive strategies that can maintain progress despite uncertainty. This paper examines the evolving landscape of development finance, identifies key structural and political challenges, and issues a call to action for coordinated, concrete efforts. Without such a shift, temporary financial shortfalls risk becoming entrenched structural gaps, further jeopardizing the 2030 Agenda.
Keywords: F35; H87; O19; 330; development finance; SDGs; 2030 Agenda; FfD Seville Conference